Intracoronary administration of nicorandil during primary percutaneous coronary intervention: Impact on restoration of regional myocardial perfusion in reperfused myocardium during the subacute phase of myocardial infarction. (1st September 2015) - Takabatake, Wataru; Noma, Takahisa; Iwado, Yasuyoshi; Ishikawa, Shohei; Tobiume, Atsushi; Hasui, Yusuke; Matsunaga, Keiji; Mantani, Kaoru; Konishi, Kumi; Kawakami, Ryo; Ishihara, Naoko; Ishihara, Yasuhiro; et al.
Abstract: Background: The impact of nicorandil as adjunctive therapy for percutaneous coronary intervention (PCI) in patients with ST-elevation myocardial infarction (STEMI) is controversial. We performed 15 O-labeled water positron emission tomography (PET) to quantify regional myocardial perfusion in patients with STEMI who received nicorandil or no adjunctive therapy during PCI. Methods: PCI was performed within 8 h after STEMI onset in 33 patients. 14 patients received intracoronary nicorandil 2 mg immediately after recanalization of the culprit lesion (Nico group). After 3–4 weeks, PET was performed in which myocardial blood flow (MBF) was measured at baseline and during adenosine triphosphate (ATP)-induced hyperemia. Myocardial vascular resistance (MVR) was calculated for all segments. Data were obtained from the reperfused (Rep) and normal segments (Cont) in each patient. Results: In patients not given nicorandil (No-Nico group), the MBF was significantly lower in Rep than that in Cont at baseline and during hyperemia (Cont vs. Rep: 0.82 ± 0.14 vs. 0.68 ± 0.11, P  = 0.001, ATP-Cont vs. ATP-Rep: 2.00 ± 0.72 vs. 1.52 ± 0.61, P  = 0.017), which was restored in the Nico group (Cont vs. Rep: 0.79 ± 0.17 vs. 0.78 ± 0.20; ATP-Cont vs. ATP-Rep: 2.02 ± 0.84 vs. 1.84 ± 0.62). MVR was elevated in Rep at baseline and during hyperemia in the No-Nico group. MVR elevation in Rep was prevented in the Nico group. Conclusions: 15 O-labeled water PET was feasible for segmental analysis of MBF during the subacute phase of STEMI. It revealed that intracoronary administration of nicorandil to STEMI patients who underwent PCI prevented MVR elevation and thus restored MBF in the reperfused segments to a level similar to that in the normal segments. Highlights: 15 O-labeled water positron emission tomography (PET) is a tool to compare directly reperfused segments with normal segments simultaneously in each patient's hearts. 15 O-labeled water PET permits noninvasive quantitative measurement of myocardial blood flow during the subacute phase of myocardial infarction. 15 O-labeled water PET detects restoration of myocardial blood flow after intracoronary administration of nicorandil in STEMI patients.